2020
DOI: 10.21203/rs.3.rs-75000/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CoV2-ID, a MIQE-compliant sub-20-minute 5-plex RT-PCR assay targeting SARS-CoV-2 for the diagnosis of COVID-19

Abstract: Accurate, reliable and rapid detection of SARS-CoV-2 is essential not only for correct diagnosis of individual disease but also for the development of a rational strategy aimed at lifting confinement restrictions and preparing for possible recurrent waves of viral infections. We have used the MIQE guidelines to develop two versions of a unique fiveplex RT-qPCR test, termed CoV2-ID, that allows the detection of three viral target genes, a human internal control for confirming the presence of human cells in a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The integrity of new batches of SARS-CoV-2 RT-PCR reagents (i.e., primers, probes, PCR master mix, and DNase/RNase free water) should be confirmed before use (Bustin et al, 2020;Huggett et al, 2020). This can be achieved by analyzing 10 to 12 NTC replicates alongside a positive control for each new lot of RT-PCR reagents.…”
Section: Reagent Screening and Handlingmentioning
confidence: 99%
“…The integrity of new batches of SARS-CoV-2 RT-PCR reagents (i.e., primers, probes, PCR master mix, and DNase/RNase free water) should be confirmed before use (Bustin et al, 2020;Huggett et al, 2020). This can be achieved by analyzing 10 to 12 NTC replicates alongside a positive control for each new lot of RT-PCR reagents.…”
Section: Reagent Screening and Handlingmentioning
confidence: 99%
“…PCR has extremely high sensitivity (99%) and specificity (97%) ( 16), serving as an accepted method in diagnostic testing laboratories. The most recent report showed that by targeting three viral genes (Nsp10, NSP12, N), the PCR assays can provide 100% accuracy of test results, based on 23 COVID-19 positive samples and 5 COVID-19 negative samples (5). Variants that increase the transmission occur mostly in the spike proteins (1).…”
Section: Discussionmentioning
confidence: 99%